The Effect of Live Selling and the Double Date Campaign on Sales of Annaira Collection Gamis on Shopee - Anggi Wulan Ramadhani; Satria Veriansyah Wiguna (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the effect of live selling and the double date campaign on sales of Annaira Collection gamis on the Shopee platform. The Muslim clothing industry in Indonesia has shown significant growth, driven by an increasing Muslim population, sharia lifestyle trends, and the development of digital technology that is changing consumer behavior (Ministry of Industry, 2021; Kotler & Keller, 2016; Thomson Reuters, 2020). The live selling strategy allows real-time interaction between sellers and consumers, increasing trust and emotional engagement (Kaplan & Haenlein, 2010; Chen & Lin, 2018), while the double date campaign offers limited promotional incentives that drive purchase interest and transaction volume (Kotler & Armstrong, 2018; Zhang et al., 2020). This study uses a quantitative approach with an explanatory research method and a sample of 100 consumers selected through purposive sampling (Sugiyono, 2019; Sekaran, 2016). Data were collected through a Likert-based questionnaire and analyzed using multiple linear regression to test the partial and simultaneous effects of both promotional strategies. The results showed that live selling and the twin-date campaign each had a positive and significant effect on gamis sales, and together, these two strategies explained 92% of the sales variation. These findings underscore the importance of creative and integrated digital promotional strategies to improve sales performance of Muslim fashion products in the e-commerce era.